Predictive Probability of the Global Alignment and Proportion Score for the Development of Mechanical Failure Following Adult Spinal Deformity Surgery in Asian Patients. Issue 2 (15th January 2021) - Yagi, Mitsuru; Daimon, Kenshi; Hosogane, Naobumi; Okada, Eijiro; Suzuki, Satoshi; Tsuji, Osahiko; Nagoshi, Narihito; Fujita, Nobuyuji; Nakamura, Masaya; Matsumoto, Morio; Watanabe, Kota
Abstract : Study Design: This is a multicenter retrospective review of 257 surgically treated consecutive ASD patients who had a minimum of five fused segments, completed a 2-year follow-up (53 ± 19 yrs, females: 236 [92%]). Objective: This study aimed to validate the predictive probability of the GAP score in an Asian ASD patient cohort. Summary of Background Data: The GAP score is a recently established risk stratification model for MF following ASD surgery. However, the predictive ability of the GAP score is not well studied. This study aimed to validate the predictive probability of the GAP score in an Asian ASD patient cohort. Methods: Comparisons of the immediate postoperative GAP scores between MF the and MF-free groups were performed. We evaluated the discriminative ability of the GAP score based on the area under the receiver operating characteristic curve (AUROC). The Cuzick test was performed to determine whether there is a trend between the GAP score and the incidence of MF or revision surgery. Univariate logistic regression analyses were performed to explore the associations between the GAP score and the incidence of MF or revision surgery. Results: No difference was observed in the GAP score between the MF and MF-free groups (MF vs . MF-free; GAP: 5.9 ± 3.3 vs. 5.2 ± 2.7, P = 0.07). The Cuzick analysis showed no trend between the GAP score and the risk for MF or revision surgery. Likewise, the MF rate was not correlated with the GAP score, as shown by the ROC curve (AUC of 0.56 [95% CI 0.48–0.63], P = 0.124). Univariate logistic regression confirmed no associations between the GAP score and the incidence of MF or revision surgery (MF; moderately disproportioned [MD]: OR: 0.6 [95% CI: 0.3–1.2], P = 0.17, severely disproportioned [SD]: OR: 1.2 [95% CI: 0.6–2.3], P = 0.69, revision surgery; MD: OR: 0.8 [95% CI: 0.2–2.8], P = 0.71, SD: OR: 1.2 [95% CI: 0.9–8.7], P = 0.08). Conclusion: In this multicenter study, in an Asian ASD patient cohort, the GAP score was not associated with the incidence of MF or revision surgery. Additional studies on the predictive ability of the GAP score in different patient cohorts are warranted. Level of Evidence: 3 Abstract : This study aimed to validate the predictive probability of the global alignment and proportion (GAP) score in an Asian adult spinal deformity (ASD) patients. No difference was observed in the GAP score between the mechanical failure (MF) and MF-free groups. The GAP score was not associated with the incidence of MF or revision surgery in an Asian ASDs.